The effect of using alum mordant in wild cherry bark dyestuff for the production of UV resistant colored paper : Utjecaj aluminijskog fiksatora u bojilu od kore divlje trešnje na proizvodnju obojenog papira otpornoga na UV svjetlost - Gençer, Ayhan (Array, 2019)
Depending on the use of wood in the forest industry, wood bark is mostly peeled and used as fuel. The ash and smoke left from the burned bark causes environmental pollution. The most environmentally friendly method for waste disposal is to convert waste into a valuable commodity. In this study, cherry tree bark was used as a dyestuff in paper production. Wild cherry (Cerasus avium L.) bark was boiled with water and KOH. The purpose of using KOH is to increase the solubility of the bark compounds. The chemi-thermomechanical pulp (CTMP) was dyed using the dyestuff. The alum mordant is used to fi x the dyestuff. Paper can be exposed to external influences (mechanical, physical and biological) depending on the place of use. One of these effects is sunshine. When paper is exposed to direct or indirect sunlight, paper changes its color. Depending on the place of use, it is expected that the color of the paper will not be affected by the sunlight or that it will provide long-term strength after the application. Accelerated weathering test was chosen to measure the UV resistance of the dyestuff. The results have shown that the mordant has a significant effect on the fixation of dyestuff. After a total of 150 hours of weathering test, the color change was observed to be the lowest in the paper samples to which alum mordant was added to the dyestuff.